Diversity, Economic Value, and Conservation Status of Macroinvertebrates in the Coastal Areas of East Coast of Aceh Province, Indonesia - Tri Mustika Sarjani; Abdul L. Mawardi; Hera Irma Suryani; Anita Rasuna Sari Siregar (Postgraduate, University of Mataram, 2025)
This research aims to analyze the diversity, economic value, and conservation status of macroinvertebrates in the coastal areas of the east coast of Aceh Province. The research method involves surveying the coastal regions of the east coast of Aceh Province, with macroinvertebrate sampling conducted through purposive sampling based on varying environmental characteristics. A total of 6.056 macroinvertebrate individuals from 55 species belonging to three classes, namely Gastropoda, Bivalvia, and Crustacea, were collected from the coastal areas of Aceh. Gastropods dominated the sample, while crustaceans were the least represented. The highest utilization of macroinvertebrates comes from the Bivalvia class, reaching 100%, while the lowest comes from the Gastropoda class at only 34.62%. Overall, no macroinvertebrates living in the coastal areas of Aceh were found to be threatened with extinction, with only 10.91% having a status of least concern. In contrast, the rest have yet to be evaluated.